MOTIVASI MASKAPAI PENERBANGAN GARUDA INDONESIA MENJALIN KERJASAMA SPONSORSHIP DENGAN LIVERPOOL FOOTBALL CLUB TAHUN 2012-2015 - Tambunan, Christopher; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study describes and proves about motivation PT. Garuda Indonesia in cooperation with one of European football club namely Liverpool Football Club from 2012 to 2015. PT. Garuda Indonesia under the leadership of Emirsyah Satar.The perspective that used in this study is the neoliberal perspective. Robert McChesney (2001)said that neolibelarisme respects to very strong beliefs regarding the market's ability in uinge new technologies to solve social problems with a better result than the other alternatives. This study also uses globalization theory. This theory assumes that cross state boundaries as if no longer valid because their collaborations undertaken by countries.PT. Garuda Indonesia is an airline in Indonesia and a State Owned Enterprises who has aim in gaining economies country and help Indonesian properity. In efforts to become an international airline class that is recognized by the international community, Garuda Indonesia improves the flight quality and aviation safety. In its attempt to reach the European market, Garuda Indonesia is making and actuating cooperation with Liverpool Football Club from 2012 to 2015. In this partnership, Garuda Indonesia is having big chance promotion in the European market through a sponsorship and partnership with Liverpool Football Club that has stable brand and achievements in the premier league.Keywords: european markets, Garuda Indonesia, globalization, Liverpool Football Club, sponsorship